Cytological observation and transcriptome analysis reveal dynamic changes of Rhizoctonia solani colonization on leaf sheath and different genes recruited between the resistant and susceptible genotypes in rice - Liu, Sanglin; Wang, Tianya; Meng, Guoxian; Liu, Jiahao; Lu, Dibai; Liu, Xiangdong; Zeng, Yuxiang (Frontiers in Plant Science, 2022)
Sheath blight, caused by Rhizoctonia solani, is a big threat to global rice production. To characterize early development of R. solani on rice leaf and leaf sheath, two genotypes including GD66, a resistant genotype, and Lemont, a susceptible genotype, were observed using four cytological techniques, including the whole-mount eosin B-staining confocal laser scanning microscopy (WE-CLSM), stereoscopy, fluorescence microscopy, and plastic semithin sectioning after in vitro inoculation. WE-CLSM observation showed that at 12 hours post inoculation (hpi), the amount of hyphae increased dramatically on leaf and sheath surface, the infection cushions occurred and maintained at a huge number from about 18 to 36 hpi, then the infection cushions disappeared gradually from about 42 to 72 hpi. Interestingly, R. solani could not only colonize on the abaxial surfaces of leaf sheath but also invade the paraxial side of the leaf sheath, which show different behavior from that of leaf. RNA sequencing detected 6234 differentially expressed genes (DEGs) for Lemont and 7784 DEGs for GD66 at 24 hpi, and 2523 DEGs for Lemont and 2719 DEGs for GD66 at 48 hpi, suggesting that GD66 recruiting more genes in fighting against the pathogen. Among DEGs, resistant genes, such as OsRLCK5, Xa21 and Pid2, displayed higher expression in the resistant genotype than the susceptible genotype at both 24 h and 48 h after inoculation, which were validated by qRT-PCR. Our results indicated that the resistance phenotype of GD66 was the consequence of recruiting a series of resistance genes involved in different regulatory pathways. WE-CLSM is a powerful technique for uncovering the mechanism of R. solani invading rice, and for detecting rice sheath blight resistance germplasm.